Biological active substances of Bergenia crassifolia (L.) Fitsch and Sanguisorba officinalis L. (Experimental biology, 2015)
The aim of the research is phytochemical analysis of the main groups of biological active substances in Bergenia crassifolia and Sanguisorba officinalis growing in the East Kazakhstan . The qualitative and quantitative compound in plant leaves and roots is determined. Predominant content of tannin and flavonoids is defined. The tannin content was found 21.08% in the rhizomes S. officinalis 20.87% in the leaves B. crassifolia, 10.64% in the rhizomes B. crassifolia.The flavonoid content was highest in the leaves of B. crassifolia (2.24%).
Keywords: Bergenia crassifolia; Sanguisorba officinalis; biological active substances; tannins; flavonoid